Pencegahan dan Penanggulangan Anemia Terhadap Pengetahuan, Kepatuhan Konsumsi Tablet Tambah Darah, dan Kadar Hb pada Remaja Putri - Ni Luh Arniti; Septriana Septriana; Fera Nofiartika (POLTEKKES KEMENKES MANADO, 2021)
ABSTRACT Background: Prevalence of anemia in woman aged > 15 years old is 22,7 %. Anemia in adolescent girls is one of the health problems in Indonesia, which must be solved immediately. It will be a risk on their pregnancy and birthing. Knowledge of woman about anemia is quite low. The government efforts to reduce the prevalence of anemia through prevention and treatment programs for anemia in adolescents and woman reproductive age, by iron supplementation through school institutions. Objective: To know the effect of anemia prevention and control programs on increased knowledge, complience to iron splement consumption and Hb levels. Methods: This study was quasi-experimental study with one group pretest post-test design. The research was conducted since July until October 2019. The sample in this study were 52 female students of MAN Labuan Bajo NTT who met the inclusion criteria. Knowledge was taken by means of a test using a questionnaire, compliance was taken from the iron supplement consumption and Hb levels were taken with Easy Touch GCHb.. Statistical analysis used the Dependent t-test. Result: The results showed an increase in the value of knowledge after intervention 9.49 and an increase in Hb levels by 0.75 gr / dl. There was no difference in the number of tablets taken after the intervention. Conclusion: Prevention and treatment of anemia programe increases knowledge and Hb levels. Complience of iron suplement consumption is high because of supervision from teacher.